SAT0634-HPR Treat To Target Access, Care and Outcome: A Nurse Led Care Initiative. (15th July 2016) - Minnock, P.; ,
Abstract : Background: Contributing factors to the acknowledged inefficient clinical pathway for patients with inflammatory arthritis (IA) in Ireland include the inadequate number of practicing rheumatologists and specialist nurses (0.7 per 100, 000 and 0.5 per 135, 000 inhabitants, respectively). There is evidence that nurse led care (NLC) delivers quality care, improves access and delivers cost savings. Objectives: To address lengthy waiting lists, inefficient use of physician time, reduced patient outcome, and deliver as standard care patient centred Treat to Target (T2T) in a cost neutral/cost effective manner through NLC. Methods: The IRNF presented a business case to the Health Service Executive detailing how patient centred T2T could be realised nationally, through the implementation of 12 advanced nurse practitioner (ANP), and 29 clinical nurse specialist (CNS) posts, under the direction of consultant rheumatologists. Evidence to support this proposal as a cost neutral investment was compiled based on the secondary benefits of T2T, firstly as a NLC initiative and secondly, through improved medication optimisation/management. Results: The non–inferiority of NLC versus rheumatologist led care, and superiority with respect to satisfaction and costs is proven. In Ireland an estimated 4, 500 patients are diagnosed with IA annually, T2T requires each patient to have up to 6 reviews creating the demand for 27, 000 out-patient reviews during year 1. NLC could provide the required access for 300–600 out-patient reviews per 100, 000 head of population ($≈ $13, 500–27, 000 per annum). Optimisation of methotrexate (MTX) dosing has demonstrated both efficacy and reduced requirements for more expensive treatments in specific patients. Through nurse led MTX optimisation 12 patients in 17 rheumatology departments saved from initiation of a biologic therapy (12 x 17 x €12, 300) could provide €2.5 million savings annually. A potential national saving of €15 million through reduced biologic dosing in stable disease has already been demonstrated. Therefore, a 50% dose reduction of a biologic treatment in 10 patients could yield annual savings of €67, 500 which exceeds the maximum ANP/CNS salary scale. This evidence demonstrates that the estimated required funds (€2.9 million) could be generated and a potential saving of €13m realised from the secondary benefits of T2T, namely a NLC initiative, and improved medication optimisation. A specially commissioned electronic patient record will ensure capture of agreed health care performance statistics to demonstrate the impact on improvements in service access and costs to the implementation, as well as on patient outcome, of these additional nursing posts. Conclusions: This proposal demonstrates how this physician directed nurse led initiative to implement T2T can be realised in a cost neutral/cost effective manner. Estimated conservative and speculative benefits to the health service profit and loss account range from zero loss to circa €15 million savings, respectively. These savings will more than adequately fund the additional posts. Moreover, tighter disease management and control in early IA will lessen the requirement for more expensive treatments in the long term, and enhance patient outcome. Disclosure of Interest: P. Minnock Grant/research support from: The development of the business case was supported by an unrestricted educational grant from MSD, who partnered with the IRNF in an advisory capacity during the project